Finite Element Solutions for Magnetic Field Problems in Terfenol-D Transducers - Teng, Duo (Sensors (Basel), 2020)
An appropriate magnetic design helps ensure that the Terfenol-D (Terbium- Dysprosium-Iron alloy) rods in giant magnetostrictive transducers have the perfect magnetostriction ability. To determine the optimum Terfenol-D rod state, a segmented stack configuration comprised by the Terfenol-D rods and NdFeB (neodymium-iron-boron) permanent magnets is presented. The bias magnetic field distributions simulated through the finite element method indicate that the segmented stack configuration is one effective way to produce the desired bias magnetic field. Particularly for long stacks, establishing a majority of domain to satisfy the desired bias magnetic field range is feasible. On the other hand, the eddy current losses of Terfenol-D rods are also the crucial to their magnetostriction ability. To reduce eddy current losses, the configuration with digital slots in the Terfenol-D rods is presented. The induced eddy currents and the losses are estimated. The simulations reveal that the digital slots configuration decreases the eddy current losses by 78.5% compared to the same size Terfenol-D rod with only a hole. A Terfenol-D transducer prototype has been manufactured using a Terfenol-D rod with a mechanical prestress of about 10 MPa and a bias magnetic field of about 42 kA/m. Its maximum transmitting current response of 185.4 dB at 3.75 kHz indicates its practicability for application as an underwater projector.